The Efficacy of Combined Microneedling and Topical Poly-d,l-lactic Acid (Juvelook) Application for Facial Pore Reduction and Skin Texture Improvement - Jovian Wan, MBChB; Suk Bae Seo, MD; Song Eun Yoon, MD; Kyu-Ho Yi, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Enlarged facial pores are a common cosmetic concern influenced by factors such as age, genetics, and increased sebaceous activity. Despite the availability of numerous treatment modalities, results are often variable, and many methods involve significant discomfort or a high number of sessions. This case series evaluated the efficacy of combining microneedling with the topical application of poly-d,l-lactic acid (PDLLA, Juvelook, VAIM Inc., Seoul, Korea) in reducing pore size and improving skin texture. Methods:. Fifteen patients with enlarged facial pores underwent 3 sessions of microneedling with intradermal PDLLA injections spaced 3 weeks apart. Pore size was evaluated using a standardized visual grading scale, and improvements in skin texture were assessed through clinical photography. Patient satisfaction was measured using a 4-point Likert scale. Results:. All patients demonstrated significant improvements, with pore size scores decreasing from an average of 6 (baseline) to 3 at 12 weeks (P < 0.001) and results maintained through 22 weeks. Skin texture showed noticeable enhancement, and 80% of patients reported high satisfaction levels. Mild transient erythema and edema were observed in some patients, resolving within 48 hours. Conclusions:. Microneedling combined with topical PDLLA is a minimally invasive, effective treatment for pore reduction and skin texture improvement. Further research, including larger randomized controlled trials and advanced imaging technologies, is warranted to validate these findings and refine the treatment protocol.